RANCANG BANGUN SISTEM INFORMASI PEMETAAN FLORA DAN FAUNA TAMAN HUTAN RAYA NURAKSA DENGAN MODEL ARSITEKTUR MICROSERVICES - Raihan, Yusril; Afwani, Royana; Agitha, Nadiyasari (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
The Great Forest Park (Tahura) Nuraksa has a lot of flora and fauna in it. Currently, Tahura Nuraksa does not yet have a mapping system for its flora and fauna. In the Long-Term Management Plan of Tahura Nuraksa for 2019-2029, one of which is the acceleration of completion of the mapping of Tahura Nuraksa, an indicator of success is that the making of maps supporting the management of the area can be completed. The solution is to build a Geographic Information System of flora and fauna based on microservices architecture. The system uses the Extreme Programming method. The system is built using the React JS framework for websites and React Native for mobile, and the MongoDB database. Testing services using Postman tools, testing website features using Selenium tools, and testing mobile applications using black boxes. equivalence partition and Mean Opinion Score to measure the feasibility of the system based on the point of view of the officers and the point of view of the tourists. The assessment from the officers got the results of 71% Strongly Agree, and 29% Agree. Based on the point of view of tourists, the results obtained are 47.9% Strongly Agree, 43% Agree, and 3.8% Neutral